A LITERATURE STUDY OF PARAMEDICS’ ATTITUDES AND PERSPECTIVES OF END-OF-LIFE CARE - Bhim Singh , Manjot Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper focuses on End-of-life care is not a new or unfamiliar arena for paramedics. According to one study, almost 60% of paramedics visit a dying patient every other shift. As a result, this statistic should be taken with a grain of salt.Paramedics are likely to encounter a family member or friend of a patient who is concerned about their health and frequently expresses melancholy, despite a lack of statistics in this area. Patients may have little choice but to use ambulance services when community and 24-hour services are in upheaval, as pointed out by.Keywords: paramedics, biological paradigm, emergency service